The Effectiveness of Non-Pharmacological Interventions in Reducing Pain and Anxiety during Post-Anesthesia Recovery - Nurfatma Awalliyah Habib; Husriawan (Jurnal Ilmu Kesehatan Nusantara, 2026)
Background: Pain and anxiety are common problems during post-anesthesia recovery and may delay mobilization, reduce patient satisfaction, and negatively affect overall recovery. Non-pharmacological interventions offer safe, simple, and inexpensive complementary strategies for managing these conditions. Research Objective: This study aimed to determine the effectiveness of structured non-pharmacological interventions in reducing pain and anxiety among patients during post-anesthesia recovery. Methods: This quantitative study used a quasi-experimental pretest–posttest control group design. Sixty postoperative patients at Baubau City Regional General Hospital were selected through consecutive sampling and assigned to intervention and control groups, with 30 participants in each group. The intervention consisted of slow deep breathing, calming music, therapeutic communication, and comfort positioning for 20 minutes. Pain was measured using the Numeric Rating Scale, while anxiety was assessed using the Visual Analogue Scale for Anxiety. Data were analysed using paired, independent, and repeated-measures statistical tests. Results: The mean pain score in the intervention group decreased from 6.10 to 3.03, while the control group decreased from 5.93 to 4.47. Anxiety scores decreased from 6.03 to 2.87 in the intervention group and from 5.87 to 4.37 in the control group. Differences in pain and anxiety reductions between groups were statistically significant (p < 0.001). Conclusion: Structured non-pharmacological interventions effectively reduced pain and anxiety during post-anesthesia recovery. Their integration into routine nursing care is recommended as a complement to standard pharmacological management.